2021
DOI: 10.3389/fpsyg.2021.710984
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Forgiveness at Work: A Longitudinal Investigation of the Time-Lagged Relations Between Forgiveness and Work Outcomes

Abstract: Forgiveness has received increasing attention in the work context. Although recent cross-sectional studies have found a positive link between forgiveness and work outcomes, further research examining the temporal dynamics between these variables is needed to establish causality. This preregistered panel study investigated the time-lagged relations between forgiveness and work outcomes, and specifically addressed the question whether forgiving a coworker benefits work outcomes. Longitudinal survey data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
(112 reference statements)
2
5
0
Order By: Relevance
“…The participants were recruited through Credamo, an online research platform for data collection. This method has been shown to be effective for obtaining high-quality data and has been widely used by organizational scholars (e.g., Cao et al, 2021). Only adults in China were eligible for selection.…”
Section: Samplementioning
confidence: 99%
“…The participants were recruited through Credamo, an online research platform for data collection. This method has been shown to be effective for obtaining high-quality data and has been widely used by organizational scholars (e.g., Cao et al, 2021). Only adults in China were eligible for selection.…”
Section: Samplementioning
confidence: 99%
“…Second, our findings suggest that the trajectory of forgiveness over time is predicted by time-varying proximal variables that are related to the qualities of the interpersonal relationship and the offense. That is, we found that an increase in perceived work relationship quality after the offense also predicted an increase of forgiveness, which is in line with previous research showing strong associations between work relationship quality and forgiveness (e.g., Cao et al, 2021a;2021b). Thus, organizations and managers should focus on building and maintaining crucial social relationships in the workplace.…”
Section: Practical Implicationssupporting
confidence: 91%
“…In recent years, the topic of forgiveness at work has received increasing attention from scientific scholars (Faldetta, 2021;Zipay et al, 2021). These findings generally show that forgiveness is an effective way to address workplace mistreatment, maintain good work relationships (Thompson & Audrey Korsgaard, 2019) and achieve better work outcomes (e.g., job satisfaction, work engagement, and performance; Cao et al, 2021aCao et al, , 2021bToussaint et al, 2018). Forgiveness can be defined as a prosocial change toward the offender despite the offender's hurtful actions (e.g., McCullough, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These new insights may be of help to improve relationships, productivity and other positive outcomes at the workplace. They may also help employers to develop forgiveness-based interventions aimed at relieving their employees from emotional constraints and instability in work relationships (Cao et al, 2021). These, in turn, may enhance their job satisfaction, work engagement, creativity, cooperation, commitment, productivity and well-being (Cao et al, 2021) and may reduce aggression and burnout at the workplace (Liao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%